2020
DOI: 10.1089/lap.2019.0607
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Orchiopexy Versus Open Orchiopexy for Palpable Undescended Testis in Children: A Prospective Comparison Study

Abstract: Background: Can laparoscopic orchiopexy achieve a better testicular position and a higher success rate than open orchiopexy for palpable undescended testis in children? We conducted a prospective comparison study with a large volume of cases to answer this question. Methods: A total of 256 patients with palpable undescended testis who were admitted between January 1, 2017 and December 31, 2017 were included in this study. Among them, 124 patients underwent laparoscopic orchiopexy and 132 patients underwent ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 13 publications
1
30
0
1
Order By: Relevance
“…They have highlighted all the benefits of minimally invasive surgery as the main advantage of LO together with the possibility of contralateral inguinal canal exploration in cases of patent processus vaginalis [11,[14][15][16][17][18][19][20][21]. The rates of complications, especially in regard to testicular atrophy and ascent after surgery were similar to the open approach in the majority of the published studies [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…They have highlighted all the benefits of minimally invasive surgery as the main advantage of LO together with the possibility of contralateral inguinal canal exploration in cases of patent processus vaginalis [11,[14][15][16][17][18][19][20][21]. The rates of complications, especially in regard to testicular atrophy and ascent after surgery were similar to the open approach in the majority of the published studies [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 90%
“…Subsequently, several authors have reported similar safety and efficacy with LO as compared to the conventional open orchiopexy (CO) for the management of inguinal undescended testicles [11,[14][15][16][17][18][19][20][21]. They have highlighted all the benefits of minimally invasive surgery as the main advantage of LO together with the possibility of contralateral inguinal canal exploration in cases of patent processus vaginalis [11,[14][15][16][17][18][19][20][21]. The rates of complications, especially in regard to testicular atrophy and ascent after surgery were similar to the open approach in the majority of the published studies [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Various minimally invasive procedures are performed to treat inguinal cryptorchidism to meet patients' aesthetic requirements. Laparoscopic orchiopexy has been the gold standard for the treatment of abdominal cryptorchidism and can also be performed for inguinal cryptorchidism to achieve an aesthetic effect [4][5][6][7][8][9][10] . Orchiopexy via a single scrotal incision can also be performed for inguinal cryptorchidism to improve the appearance [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Various minimally invasive procedures are performed to treat inguinal cryptorchidism to meet patients' aesthetic requirements. Laparoscopic orchiopexy has been the gold standard for the treatment of abdominal cryptorchidism and can also be performed for inguinal cryptorchidism to achieve an aesthetic effect [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%